Urinary incontinence, its risk factors, and quality of life: A study among women aged 50 years and above in a rural health facility of West Bengal - Bijit Biswas; Aritra Bhattacharyya; Aparajita Dasgupta; Anubrata Karmakar; Nazrul Mallick; Sembagamuthu Sembiah (Wolters Kluwer Medknow Publications, 2017)
Context: Urinary incontinence (UI) is a chronic debilitating disease which is often under reported, but laid significant impact on one's quality of life (QoL) thus is of public health importance. Aims: The aim of this study is to find out proportion of rural women have UI, its associated risk factors and treatment-seeking behavior, QoL of affected women. Methods: This was a cross-sectional clinic-based study conducted from October 2016 to January 2017 among 177 women aged 50 years or above attending a rural health facility with a structured schedule. Data were analyzed using appropriate statistical methods by SPSS (version 16). Results: Forty-nine (27.7%) out of 177 women were found having UI. The most prevalent type of UI was stress UI (51.0%), followed by mixed UI (32.7%) and urge UI (16.3%). In bivariate analysis, study participants who were illiterate, having a history of prolonged labor, having a history of gynecological operation, normal vaginal deliveries (NVDs) (>3), diabetic, having chronic cough, having constipation, and having lower urinary tract symptoms (LUTS) had shown significantly greater odds of having UI. In multivariable illiteracy (adjusted odds ratio [AOR] - 2.41 [1.02-5.69]), NVDs (AOR - 3.37 [1.54-7.37]), a history of gynecological operation (AOR - 3.84 [1.16-12.66]), chronic cough (AOR - 2.69 [1.21-5.99]), LUTS (AOR - 2.63 [1.15-6.00]) remained significant adjusted with other significant variable in bivariate analysis. Those with mixed UI had 5.33 times higher odds having unfavorable QoL. Only 30.6% sought medical help. Treatment-seeking behavior shown negative correlation with QoL while fecal incontinence and LUTS shown possitive correlation. Conclusions: The study revealed that rural women are indeed at high risk of developing UI. Majority of them did not sought treatment for UI which is matter of concern. Generating awareness regarding UI may help to improve health-seeking behavior and QoL.